2010
DOI: 10.1007/s11595-010-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal preparation and photocatalytic water splitting properties of ZrW2O8

Abstract: ZrW 2 O 8 was prepared by adjusting Zr︰W mole ratio and HCl concentration in hydrothermal reaction processes. The obtained sample was crystallized in α-ZrW 2 O 8 phase (cubic, P2 1 3), with band gap energy of 4.0 eV. The properties of photocatalytic water splitting were examined under UV light irradiation. The average rate of H 2 evolution over 0.3wt% Pt/ZrW 2 O 8 in the presence of CH 3 OH as electron donor (ED) was 23.4 μmol/h, while the average rate of O 2 evolution over ZrW 2 O 8 in the presence of AgNO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…[3][4][5][6][7] In experiments, the phase transition, specific heat, thermal expansion of ZrW 2 O 8 have been studied by some groups [8][9][10][11] , especially for the temperature-and pressure-induced phase transitions, and the temperature-dependence of the thermal. [12][13][14] For example, it has long been noticed that α- The following electronic band structure calculation by GGA (not shown here) indicates the existence of an indirect band gap, whose value E g is about 3.31eV, larger than other theoretical result, e.g., 2.84eV by LDA, 18 more coincides with the experimental value, i.e., 4.0eV, 20 , which is smaller than the experimental value due to the well-known underestimate of conduction-band energies in ab initio calculations.…”
Section: ⅰ Introductionsupporting
confidence: 62%
“…[3][4][5][6][7] In experiments, the phase transition, specific heat, thermal expansion of ZrW 2 O 8 have been studied by some groups [8][9][10][11] , especially for the temperature-and pressure-induced phase transitions, and the temperature-dependence of the thermal. [12][13][14] For example, it has long been noticed that α- The following electronic band structure calculation by GGA (not shown here) indicates the existence of an indirect band gap, whose value E g is about 3.31eV, larger than other theoretical result, e.g., 2.84eV by LDA, 18 more coincides with the experimental value, i.e., 4.0eV, 20 , which is smaller than the experimental value due to the well-known underestimate of conduction-band energies in ab initio calculations.…”
Section: ⅰ Introductionsupporting
confidence: 62%
“…In search of tungsten compounds that are stable under hydrothermal conditions, references to zirconium tungsten oxides were found. In the literature, under hydrothermal conditions, produced tungsten and zirconia containing material can be found . The hydrothermal preparation by Hui and co‐workers produced well crystalline ZrW 2 O 8 grains for the photocatalytic water splitting with a low Brunauer–Emmett–Teller (BET) surface area of 3.58 m 2 g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, under hydrothermal conditions, produced tungsten and zirconia containing materialc an be found. [26][27][28] The hydrothermal preparation by Hui and co-In this work, we describe ac atalytic material based on az irconium-tungsten oxide with ruthenium for the hydrogenolysis of microcrystalline cellulose under hydrothermal conditions. With these catalysts, polyols can be produced with high yields.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, n is determined by the type of optical transition of a semiconductor (n = 1 for direct transition and n = 4 for indirect transition). For cubic ZrMo 2 O 8 , it has the same crystal structure with cubic ZrW 2 O 8 which bears indirect transition, so the value of n is 4 [28]. It is reported that light absorption generates an electron in the conduction band and a positive hole in the valence band [29].…”
Section: Uv-vis Spectra and Photocatalysismentioning
confidence: 99%